Efektifitas Penerapan Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan di Kantor Urusan Agama Kecamatan Bendosari Kabupaten Sukoharjo - Supriyanto, Supriyanto; Budi Wibowo, Muhammad Kurniawan; Baehaqi, Baehaqi (STAINI Press, 2024)
Marriage is a way for creatures to preserve life, after each partner is ready to play a positive role in realizing the goal of marriage. Phenomena related to the age limit for marriage in Indonesia are still an interesting matter to study, bearing in mind that legal regulations regarding marriage (Law No. 1 of 1974 which was renewed by Law No. 16 of 2019) are still not effective in preventing marriage under age (early marriage). This study aims to analyze the effectiveness of applying Law Number 16 of 2019 in controlling underage marriages and the factors that influence the effectiveness of implementing Law Number 16 of 2019 in controlling underage marriages.This research is a qualitative descriptive research aimed at getting an overview of the effectiveness and factors that influence the effectiveness of the application of Law Number 16 of 2019 in controlling underage marriages. Data collection techniques in this study used direct surveys, interviews and documentation studies. The data analysis technique used in this study uses interactive descriptive analysis.The results of this study draw the conclusion that the application of Law Number 16 of 2019 concerning Marriage has been effective in controlling early marriage in the KUA area of Bendosari Sukoharjo Sub-District which has been proven to be able to reduce the incidence of early marriage which was originally an average of 11 events per year to an average of 5 incidents per year, and the effectiveness of the application of Law Number 16 of 2019 Concerning Marriage in controlling early marriage in the KUA area of Bendosari Sukoharjo District is influenced by several factors such as the legal factor of the law itself, the factor of law enforcement agencies or the parties involved, the facility factor (facilities and infrastructure supporting law enforcement), cultural factors and community factors